Experimental research on influence of interstage oil injection in a dual-motor-driven two-stage screw air compressor. Issue 1 (1st November 2022) - Liao, X; Wang, C; Yuan, H; Xing, Z
Abstract : Energy saving for compressed air production is of great importance all over the world due to its great energy cost and the indispensable utility of compressed air in the industrial sector. In recent years, oil-injected two-stage screw air compressors, especially driven by dual motors, are becoming a promising alternative to other compression equipment for their extraordinary efficiency and high reliability in a wide range of applications. However, two-stage screw air compressors have a different and complicated oil injection system compared with single-stage compressors. And an appropriate setting of oil injection parameters might result in a considerable performance improvement of the compressor. In this paper, a dual-motor-driven two-stage oil-injected screw compressor was tested under the actual service conditions and control modes experimentally. The effect of interstage oil injection on the compressor performance was studied in detail by varying the interstage oil injection flow rate and rotating speed. The performance parameters such as specific power, volumetric efficiency and adiabatic efficiency were calculated from the measured data. The results indicate that an excess amount of oil exists in the second stage compressor and reducing the oil moderately could decrease the power consumption of the two-stage air compressor unit.